Long-term efficacy and safety of subcutaneous pasireotide alone or in combination with cabergoline in Cushing’s disease - Feelders, Richard A.; Fleseriu, Maria; Kadioglu, Pinar; Bex, Marie; González-Devia, Deyanira; Boguszewski, Cesar Luiz; Yavuz, Dilek Gogas; Patino, Heather; Pedroncelli, Alberto M.; Maamari, Ricardo; Chattopadhyay, Arghya; Biller, Beverly M. K.; et al. (Frontiers in Endocrinology, 2023)
Objective: This study evaluated short-and long-term efficacy and safety of the second-generation somatostatin receptor ligand pasireotide alone or in combination with dopamine agonist cabergoline in patients with Cushing's disease (CD).This is an open-label, multicenter, non-comparative, Phase II study comprising 35-week core phase and an optional extension phase. All patients started with pasireotide, and cabergoline was added if cortisol remained elevated. Eligible patients had active CD, with or without prior surgery, were pasireotide naïve at screening or had discontinued pasireotide for reasons other than safety. Primary endpoint was proportion of patients with a mean urinary free cortisol (mUFC) level not exceeding the upper limit of normal (ULN) at week 35 with missing data imputed using last available post-baseline assessments.Results: Of 68 patients enrolled, 26 (38.2%) received pasireotide monotherapy and 42 (61.8%) received pasireotide plus cabergoline during the core phase. Thirty-four patients (50.0%; 95% CI 37.6-62.4) achieved the primary endpoint, of whom 17 (50.0%) received pasireotide monotherapy and 17 (50.0%) received combination therapy. Proportion of patients with mUFC control remained stable during the extension phase up to week 99. Treatment with either mono or combination therapy provided sustained improvements in clinical symptoms of hypercortisolism up to week 99. Hyperglycemia and nausea (51.5% each), diarrhea (44.1%) and cholelithiasis (33.8%) were the most frequent adverse events.Conclusions: Addition of cabergoline in patients with persistently elevated mUFC on maximum tolerated doses of pasireotide is an effective and well-tolerated long-term strategy for enhancing control of hypercortisolism in some CD patients.